Chondroitin sulfate and sulfated hyaluronan‐containing collagen coatings of titanium implants influence peri‐implant bone formation in a minipig model. Issue 7 (30th August 2013) - Korn, P.; Schulz, M. C.; Hintze, V.; Range, U.; Mai, R.; Eckelt, U.; Schnabelrauch, M.; Möller, S.; Becher, J.; Scharnweber, D.; Stadlinger, B.
Abstract An improved osseous integration of dental implants in patients with lower bone quality is of particular interest. The aim of this study was to evaluate the effect of artificial extracellular matrix implant coatings on early bone formation. The coatings contained collagen (coll) in conjunction with either chondroitin sulfate (CS) or sulfated hyaluronan (sHya). Thirty‐six screw‐type, grit‐blasted, and acid‐etched titanium implants were inserted in the mandible of 6 minipigs. Three surface states were tested: (1) uncoated control (2) coll/CS (3) coll/sHya. After healing periods of 4 and 8 weeks, bone implant contact (BIC), bone volume density (BVD) as well as osteoid related parameters were measured. After 4 weeks, control implants showed a BIC of 44% which was comparable to coll/CS coated implants (48%) and significantly higher compared to coll/sHya coatings (37%, p = 0.012). This difference leveled out after 8 weeks. No significant differences could be detected for BVD values after 4 weeks and all surfaces showed reduced BVD values after 8 weeks. However, at that time, BVD around both, coll/CS (30%, p = 0.029), and coll/sHya (32%, p = 0.015), coatings was significantly higher compared to controls (22%). The osteoid implant contact (OIC) showed no significant differences after 4 weeks. After 8 weeks OIC for controls was comparable to coll/CS, the latter being significantly higher compared to coll/sHya (0.9% vs. 0.4%, p = 0.012). There were no significant differences in osteoid volume density. In summary, implant surface coatings by the chosen organic components of the extracellular matrix showed a certain potential to influence osseointegration in vivo. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 102A: 2334–2344, 2014.